2005
DOI: 10.1002/cncr.21240
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neutropenia on the impact of a cognitive‐behavioral intervention for symptom management

Abstract: BACKGROUNDTrials of cognitive‐behavioral interventions (CBI) designed to reduce symptom severity or improve dimensions of quality of life seldom consider how the side effects of treatment or the complications imposed by the disease or treatment may moderate the impact of the trial on the designated outcome. To address this issue, the moderating effect of neutropenia on the impact of a CBI for reducing symptom severity was evaluated among patients with cancer undergoing chemotherapy.METHODSThe authors described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…In the study by Andersen et al (2008), small group interventions provided strategies to reduce stress, improve mood, improve health behaviors and maintain adherence to cancer treatment, which provided both psychological support and behavioral education [11]. In the present study, a problem-solving cognitive behavioral intervention was used to reduce symptom severity in participants undergoing chemotherapy for solid tumors [25][26][27]. Whereas other studies used group therapy as a delivery method, in the present study, cognitive behavioral intervention was delivered though individual contact using weekly phone calls.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the study by Andersen et al (2008), small group interventions provided strategies to reduce stress, improve mood, improve health behaviors and maintain adherence to cancer treatment, which provided both psychological support and behavioral education [11]. In the present study, a problem-solving cognitive behavioral intervention was used to reduce symptom severity in participants undergoing chemotherapy for solid tumors [25][26][27]. Whereas other studies used group therapy as a delivery method, in the present study, cognitive behavioral intervention was delivered though individual contact using weekly phone calls.…”
Section: Discussionmentioning
confidence: 98%
“…Details of the intervention and outcomes were described in previous publications [25][26][27] . This secondary analysis was reviewed and approved by the institutional review board at the University of Pittsburgh.…”
Section: Methodsmentioning
confidence: 99%
“…As with exercise interventions, a growing body of empiric data supports the use of psychosocial interventions for the management of CRF. Randomized, controlled clinical trials have examined a variety of psychosocial interventions in cancer survivors during and after treatment (Table 2) [139][140][141][142][143][144][145][146][147][148][149][150][151][152][153].…”
Section: Psychosocial Interventionsmentioning
confidence: 99%
“…Participants reported interference in their daily activities due to CIN, negative emotions, social isolation, and a reduced sense of self-worth. In a recent randomized trial of an intervention to improve cancer symptom management, Given et al [13] found that neutropenia modulated the effect of the intervention on symptom severity. Patients with CIN did not experience an improvement in their symptoms, while patients without CIN did improve with the symptom management intervention.…”
Section: Introductionmentioning
confidence: 99%